Modulation of maintenance and processing in working memory by negative emotions. - Chainay, Hanna; Ceresetti, Romain; Pierre-Charles, Carl; Plancher, Gaën (Memory & Cognition, 2023)
Previous research has shown that working memory processes are affected by emotions. However, it is not clear if both components – maintenance and processing of information – are modulated by emotion. Since emotion is intimately related to attention, we focused on attentional maintenance in working memory. In a previous study, using a complex span task, we showed that processing emotionally negative information reduced maintenance of neutral information in working memory. The objective of the present study was first to replicate the results of our previous study and second to investigate whether maintaining emotional information would affect processing of neutral information. In Experiment 1, young adults were asked to remember a series of five letters each followed by images, either negative or neutral, to be categorized. In Experiment 2, participants were required to memorize a series of five images, either negative or neutral, each followed by digits to be categorized. In order to focus on attentional maintenance, in both experiments the tasks were performed under continuous articulatory suppression. In Experiment 1, longer processing times were observed for emotional stimuli than neutral ones, and lower recall of series of letters when negative stimuli were processed. In Experiment 2, higher memory performance was observed for negative images than neutral ones and longer processing times of digits when a series of negative stimuli was maintained. Overall, our results show that emotion impacts both processing and attentional maintenance in working memory. This is consistent with models of working memory suggesting an attentional trade-off between maintenance and processing.